An Insight into Acute Pericoronitis and the Need for an Evidence-Based Standard of Care - Chelsea Wehr (Dentistry Journal, 2019)
Background: Pericoronitis is inflammation of the operculum associated with a partially erupted third molar. It is a highly prevalent infection of the oral cavity and presents as a painful sensation of the soft tissue encompassing the crown of the involved tooth. Though pericoronitis is common, there is no evidence-based standard-of-care for treatment of emergency patients with acute pericoronitis. Study Design: In this study, anonymous clinicians were asked to participate in an online survey with questions formulated to identify professional clinical background, emergency treatment preferred for acute pericoronitis, number of associated complications, frequency of third molar extraction, and patient satisfaction. Results and Conclusion: A statistical analysis of the collected data regarding the variance among different treatment plans and associated complications revealed little consensus in the treatment of pericoronitis. The lack of consistency of the responses focusing on the preferred treatment for emergency patients with acute pericoronitis reinforces the need for developing a standard-of-care to train future dental professionals based on well-designed randomized controlled clinical trials and meta-analyses. Practical Implications: The ultimate goal is developing a treatment option with the fewest complications to provide the best health care for patients with pericoronitis. This issue is seen not only as an acute infection but also has the potential to impact overall health.